GameMaker game programming with GML : learn GameMaker Language programming concepts and script integration with GameMaker: Studio through hands-on, playable examples /: learn GameMaker Language programming concepts and script integration with GameMaker: Studio through hands-on, playable examples. (2014) - Unknown
No abstract available